Global engineering and construction - Yates, J. K. (John Wiley & Sons, 2007)
The first book written for operations-level engineers, constructors, and students, Global Engineering and Construction is an essential manual for navigating the confusing world of engineering and construction in the global arena and for working on multinational teams. From project management to finance, global construction to alliances, international standards to competitiveness, this book contains country- and region-specific information on cultural issues, legal systems, bid estimates, scheduling, business practices, productivity improvement, and tips for successfully working on and managing global projects. This book also provides a useful glossary and numerous case studies illustrating practices in the real world.